2023
DOI: 10.1371/journal.pone.0280912
|View full text |Cite
|
Sign up to set email alerts
|

Minimal clinically-important differences for the ‘Liverpool Osteoarthritis in Dogs’ (LOAD) and the ‘Canine Orthopedic Index’ (COI) client-reported outcomes measures

Abstract: Client-reported outcomes measures (CROMs) have been previously validated for the evaluation of canine osteoarthritis. A published systematic review indicated that the ‘Liverpool Osteoarthritis in Dogs’ (LOAD) and the ‘Canine Orthopedic Index’ (COI) can be recommended for use in dogs with osteoarthritis; these CROMs have also been used in the context of measuring surgical outcomes of dogs with orthopaedic conditions. However, the minimal clinically-important differences (MCIDs) for these CROMs have not been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…With the CBPI, a reduction of ≥1 in PSS and ≥2 in PIS was considered a clinically-important change [41]. The same level has been determined for the LOAD and COI, suggested as a reduction of ≥4 and ≥14, respectively [42]. Unreported data from our group indicate that clinically important changes consist of improvements of ≥1 for deviation and ≥10 for SI in dogs with OA.…”
Section: Resultsmentioning
confidence: 57%
“…With the CBPI, a reduction of ≥1 in PSS and ≥2 in PIS was considered a clinically-important change [41]. The same level has been determined for the LOAD and COI, suggested as a reduction of ≥4 and ≥14, respectively [42]. Unreported data from our group indicate that clinically important changes consist of improvements of ≥1 for deviation and ≥10 for SI in dogs with OA.…”
Section: Resultsmentioning
confidence: 57%
“…This evaluation was performed with clinical data available from a clinical setting caring for working police dogs, submitted to different treatments. As for referenced studies looking at determining MCIDs for other clinical outcome instruments [ 27 , 28 ], although we selected a +15 d follow-up moment, this specific follow-up time-point should not be considered a recommendation for post-treatment evaluation in dogs with OA. Rather, it was a time-point chosen based on the previous experience of the clinicians, previous conducted research, and expectation that it would be enough time to obtain a response to treatment and therefore produce different answers to the anchor question, allowing us to estimate the MCID.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the information presented in the present study was collected during a different project but has not been reported before [ 22 , 23 , 24 , 25 , 26 ]. In this study, we followed a similar methodology outlined in published papers, looking at determining minimal clinically important differences for two client-reported outcomes measures (the Liverpool Osteoarthritis in Dogs—LOAD—and the Canine Orthopedic Index—COI), in dogs with osteoarthritis and following surgery for cranial cruciate ligament rupture [ 27 , 28 ]. For included animals, an anchor question was collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personally, I feel such ‘drift’ from the original validated tool to be unhelpful. Such fundamental differences are going to cause confusion in the literature and also have consequences in light of other CROMs metrics, such as ‘minimal clinically‐important differences’ 10,11 . Given that regulatory authorities such as the European Medicines Agency and the US Food and Drug Administration are now using validated CROMs in pivotal field studies, correct administration and scoring of CROMs is essential.…”
mentioning
confidence: 99%